2015
DOI: 10.18632/oncotarget.3457
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-ATB promotes trastuzumab resistance and invasion-metastasis cascade in breast cancer

Abstract: Trastuzumab resistance is leading cause of mortality in HER2-positive breast cancers, and the role of TGF-β-induced epithelial-mesenchymal transition (EMT) in trastuzumab resistance is well established, but the involvement of lncRNAs in trastuzumab resistance is still unknown. Here, we generated trastuzumab-resistant breast cancer cells with increased invasiveness compared with parental cells, and observed robust epithelial–mesenchymal transition (EMT) and consistently elevated TGF-β signaling in these cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
236
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(245 citation statements)
references
References 37 publications
6
236
0
Order By: Relevance
“…24 Lnc-ATB was the most remarkably up-regulated lncRNA in the tissues of breast cancer patients with trastuzumab resistance and could induce invasion-metastasis cascade in breast cancer. 25 We here in Wilms tumour found that LINC00473…”
mentioning
confidence: 85%
“…24 Lnc-ATB was the most remarkably up-regulated lncRNA in the tissues of breast cancer patients with trastuzumab resistance and could induce invasion-metastasis cascade in breast cancer. 25 We here in Wilms tumour found that LINC00473…”
mentioning
confidence: 85%
“…Trastuzumab (Herceptin) was obtained from Roche (Basel, Switzerland) and dissolved in sterile water. Trastuzumab‐resistant SKBR‐3/Tr and BT474/Tr cells were obtained by continuous culture with 5 mg/mL trastuzumab for 6 months as previously reported,11, 12 and were cultured in RPMI 1640 medium with 250 μg/mL trastuzumab.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, emerging evidence indicates that they play important roles in regulating cellular and biological functions. LncRNAs can regulate gene expression at post‐transcriptional level via sponging microRNAs10 and modulate transcriptional gene silencing via the chromatin regulation 11, 12. Thus, the investigation of the role of lncRNAs in breast cancer could help with the understanding of tumorigenesis and the identification of novel diagnostic and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR-200c treatment of xenografts of a trastuzumab-resistant breast cancer cell line leads to re-gain of trastuzumab sensitivity [88]. In the same scenario, another level of regulation comes from a long non-coding RNA, Lnc-ATB, which is expressed at the downstream of TGF-β signaling and competitively binds to miR-200c conferring ZEB1 and ZNF217 (upregulation)-mediated trastuzumab resistance [89]. In summary, these studies clearly provide the cue that miR-200c could efficiently control the response of cancer cells to anti-cancer therapies through EMT-dependent and EMT-independent pathways.…”
Section: Mir-200c Emt and Targeted Therapy Resistancementioning
confidence: 99%